The Effectiveness and Safety of a Homeopathic Medicinal Product in Pediatric Upper Respiratory Tract Infections With Fever: A Randomized Controlled Trial. (30th June 2016) - van Haselen, Robert; Thinesse-Mallwitz, Manuela; Maidannyk, Vitaliy; Buskin, Stephen L.; Weber, Stephan; Keller, Thomas; Burkart, Julia; Klement, Petra
We investigated the clinical effectiveness of a homeopathic add-on therapy in a pediatric subpopulation with upper respiratory tract infections (URTI) in a randomized, controlled, multinational clinical trial. Patients received either on-demand symptomatic standard treatment (ST-group) or the same ST plus a homeopathic medication (Influcid; IFC-group) for 7 days. Outcome assessment was based on symptom and fever resolution and the Wisconsin Upper Respiratory Symptom Survey–21 (WURSS-21). A total of 261 pediatric (<12 years) patients (130 IFC-group; 131 ST-group) were recruited in Germany and the Ukraine. The IFC-group used less symptomatic medication, symptoms resolved significantly earlier ( P = .0001), had higher proportions of fever-free children from day 3 onwards, and the WURSS-assessed global disease severity was significantly less ( P < .0001) during the entire URTI episode. One adverse event (vomiting) was possibly related to IFC. IFC as add-on treatment in pediatric URTI reduced global disease severity, shortened symptom resolution, and was safe in use.